Remote Internal Audit Management Strategy with Design Thinking as A Theoretical Lens - Edwarivel, Edwarivel; Rukmana, Ovalia (International Journal of Islamic Business and Management Review, 2025)
As one of financial institutions, PT PNM is obliged to conduct internal audit as a way of responsibility to its consumers. However, during COVID 19 pandemic the internal audit was conducted remotely. Purpose – This paper aims to evaluate the remote internal audit strategy conducted in PNM using design thinking as theoretical lens. Methodology/approach – This paper adopts qualitative approach. Interviews were carried out to six participants to gain their perceptions on how they conduct remote internal audit. Data was analyzed using thematic analysis which was aided with NVivo Pro 12. Findings – It reveals that remote internal audit conducted by PT PNM ran effectively and efficiently. It is found that the adoption of ICT (information and communication technology) is required in conducting remote internal audit. Additionally, the results indicate there are both external and internal factors affect internal auditors’ performance in conducting remote audit Novelty/value – It is essential for companies to conduct remote audit in certain circumstances. Therefore, this study is expected to shed the light on the implementation of remote audit by integrating design thinking.